Student motivation in basketball learning using the inquiry learning model - Fitri Maharani; Irwan Hermawan; Asep Angga Permadi (Mamaos: Journal Physical Education, Sport and Art, 2025)
Physical education is a learning process that utilizes physical activity as a medium to achieve educational goals. It not only utilizes physical activity to achieve the goals of physical education, but also other equally important aspects, namely psychological and social aspects, to build a better character for children. To achieve learning goals, students must be motivated in learning activities. Because learning outcomes will be optimal if students be motivated from within themselves (internal) and from outside (external). According to observations made by researchers, obstacles to student motivation can be influenced by environmental conditions. Therefore, by using the inquiry learning model, it is expected that students can increase their motivation in learning influenced by the inquiry learning model. The purpose of this study was to determine whether there was an influence on learning in cycle I and Cycle II. This study is a continuous experimental study and quantitative research using Classroom Action Research design. The population in this study were all students of SMPN 4 Tarogong Kidul Class IX-G, totaling 30 people. The sampling technique used was Purposive Sampling. Data analysis in this study used tests, observations, questionnaire tests. Based on the results of the data analysis carried out, it stated that there were changes in cycles I and II from the results of the questionnaire respondent data distributed with a percentage value of 80.0%.